2017
DOI: 10.1097/mrr.0000000000000244
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional head-mounted gaming task procedure maximizes effects of vestibular rehabilitation in unilateral vestibular hypofunction: a randomized controlled pilot trial

Abstract: Considering the emerging advantages related to virtual reality implementation in clinical rehabilitation, the aim of the present study was to discover possible (i) improvements achievable in unilateral vestibular hypofunction patients using a self-assessed head-mounted device (HMD)-based gaming procedure when combined with a classical vestibular rehabilitation protocol (HMD group) as compared with a group undergoing only vestibular rehabilitation and (ii) HMD procedure-related side effects. Therefore, 24 vesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
71
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 41 publications
9
71
0
7
Order By: Relevance
“…In particular, CPAP treatment significantly reduced the postural parameters which have been found to be more related to vestibular discharge, especially during blind vision (closed eyes condition) and challenging situations (i.e., upright position on FC). These assumptions are confirmed by the fact that body sways within low frequency intervals and surface are mainly under vestibular control [23,28,29], and patients suffering from peripheral vestibular impairments (i.e., vestibular neuritis, Meniere's disease) as well as moderate-to-severe OSA had more increased values than normal subjects [13]. Furthermore, post-treatment OSA patients demonstrated a PS reduction in those blind vision and challenging conditions involving middle and high frequency interval related to somatosensory, proprioceptive, and central nervous systems discharge [23,30] (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…In particular, CPAP treatment significantly reduced the postural parameters which have been found to be more related to vestibular discharge, especially during blind vision (closed eyes condition) and challenging situations (i.e., upright position on FC). These assumptions are confirmed by the fact that body sways within low frequency intervals and surface are mainly under vestibular control [23,28,29], and patients suffering from peripheral vestibular impairments (i.e., vestibular neuritis, Meniere's disease) as well as moderate-to-severe OSA had more increased values than normal subjects [13]. Furthermore, post-treatment OSA patients demonstrated a PS reduction in those blind vision and challenging conditions involving middle and high frequency interval related to somatosensory, proprioceptive, and central nervous systems discharge [23,30] (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…The successful use of exergaming in vestibular rehabilitation has been implemented previously ( Bergeron et al, 2015 ; Micarelli et al, 2017 ). Micarelli et al (2017) found a non-significant improvement in the VOR gain in patients with unilateral vestibular hypofunction by using a self-assessed gaming procedure with a head-mounted device ( Micarelli et al, 2017 ). The patients with Ménière’s disease in this study showed a decreasing trend in their center of gravity sway after three-dimensional VR vestibular rehabilitation ( Hsu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the field of VR-based vestibular rehabilitation, recent evidence advocated for the use of headmounted displays (HMD) in a home-based gaming program coupled with conventional adaptation, habituation and substitution exercises [5]. Unilateral vestibular hypofunction patients demonstrated a significant improvement in posturography parameters and self-report measures such as the Dizziness Handicap Inventory; interestingly, also VOR gain was significantly increased in patients undergoing VRbased gameplay, with respect to their peers treated with conventional rehabilitation alone [5]. The use of HMD-based exercises has the advantage of delivering images as the highest possible resolution, while following the user's movements [3].…”
mentioning
confidence: 99%
“…The use of HMD-based exercises has the advantage of delivering images as the highest possible resolution, while following the user's movements [3]. Visual information can be altered, asking patients to perform tasks in visually enriched environments, and vestibular stimulation can be added by incorporating head movements [1], facilitating central pre-programmed eye movements during active tasks which may contribute to gaze stability [5]. The enhancing effects of [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation